Interações predador-presa : predação, oportunismo e antipredação, testadas a partir de experimentos. - Lopes, Taise Miranda (2017)
Predator-prey interactions have been addressed in different aspects within ecology. The theory of optimal foraging presents these interactions seen in the level of individuals, to explain and even predict how predators and prey adjust their behavior in response to changes in their external and internal environments. The invasion of species in natural environments has caused several modifications in these interactions. Thus, this thesis aimed to evaluate changes in behavior of predators and prey, considering situation of species invasion. The first chapter evaluated if the invasive species Astronotus crassipinnis presents trophic opportunism in an invaded environment (upper Paraná River floodplain). For this purpose, the diet was evaluated in different stages of life (juvenile and adult) and subsequently, through an experimental approach, we evaluated the ability of the species to change its food behavior according to food availability. A potential native competitor of A. crassipinnis was submitted to the same experimental approach. The invasive species presented a generalist diet in the juvenile stage, changing to specialist (piscivorous) in adult stage. Under controlled conditions, the invasive species changed its food behavior, with preference for Macrobrachium amazonicum (prey-shrimp) in relation to Moenkhausia sanctaefilomenae (prey-fish). The native species (Hoplias sp.2), also piscivorous in the natural environment, maintained its preference for fish in a controlled environment. The second chapter evaluated the antipredatory behavior of two species of prey (fish), common in the littoral region of aquatic environments of the same floodplain, in the presence of two species of piscivorous fish, one native and another invasive to the place of origin of these fish. We evaluated the refuge use behaviors, formation of schools (isolated individuals), habitat segregation and these prey activity levels. The behaviors of individuals were evaluated in microcosms in the absence and presence of each one of the predators, native (Hoplias sp.2) and invasive (Hoplerythrinus unitaeniatus). The behavior of the prey did not show a similar pattern in the type of predator. The prey only recognized the danger and responded with antipredatory behaviors in the presence of any type of predator. Already habitat segregation behavior, prey responded more effectively to invasive predator, further segregating the habitat in the presence of this predator. Considering all the avoidance behaviors presented by the prey, it was concluded that they did not present a naiveté in front of the invading predator. Thus, this thesis contributes to the advancement of knowledge of predator-prey interactions under species invasion conditions through an experimental approach.